Towards Smart Food Distribution: Integrating Supply Chain Strategic Fit and Artificial Intelligence for National Food Independence - Viyani, Ari Okta; Zahara, Inna; Tassa, Arnes; Dika, Laira (Amkop Management Accounting Review (AMAR), 2025)
Food self-sufficiency is an essential foundation in supporting national resilience. Food distribution in Indonesia still experiences serious obstacles, such as slow delivery, fuel waste, and inefficient distribution routes. AI technology has the potential to be a strategic solution to optimize the distribution system through route efficiency, energy savings, and increased delivery speed. This study aims to: (a) Test the effect of supply chain strategic fit, performance, and AI adoption in food distributors; (b) Dig deeper into the implementation, obstacles, challenges, readiness and opportunities, as well as driving factors for AI implementation in the food supply chain in Indonesia. The method used is a mixed-method, namely a quantitative approach with SEM-PLS and a qualitative approach using N-Vivo. The results of the quantitative analysis show that AI adoption mediates the relationship between supply chain strategic fit and rice distributor performance. Furthermore, the results of the qualitative analysis also support the idea that the distribution system using AI is considered to have great potential in optimizing food distribution in Indonesia. However, this adoption has several challenges, including costs, human resources, infrastructure, regulations, differences in regional topology, privacy and security, and ethics.